Early mitochondrial dysfunction leads to altered redox chemistry underlying pathogenesis of TPI deficiency - Stacy L. Hrizo; Isaac J. Fisher; Daniel R. Long; Joshua A. Hutton; Zhaohui Liu; Michael J. Palladino (Neurobiology of Disease, 2013)
Triose phosphate isomerase (TPI) is responsible for the interconversion of dihydroxyacetone phosphate to glyceraldehyde-3-phosphate in glycolysis. Point mutations in this gene are associated with a glycolytic enzymopathy called TPI deficiency. This study utilizes a Drosophila melanogaster model of TPI deficiency; TPIsugarkill is a mutant allele with a missense mutation (M80T) that causes phenotypes similar to human TPI deficiency. In this study, the redox status of TPIsugarkill flies was examined and manipulated to provide insight into the pathogenesis of this disease. Our data show that TPIsugarkill animals exhibit higher levels of the oxidized forms of NAD+, NADP+ and glutathione in an age-dependent manner. Additionally, we demonstrate that mitochondrial redox state is significantly more oxidized in TPIsugarkill animals. We hypothesized that TPIsugarkill animals may be more sensitive to oxidative stress and that this may underlie the progressive nature of disease pathogenesis. The effect of oxidizing and reducing stressors on behavioral phenotypes of the TPIsugarkill animals was tested. As predicted, oxidative stress worsened these phenotypes. Importantly, we discovered that reducing stress improved the behavioral and longevity phenotypes of the mutant organism without having an effect on TPIsugarkill protein levels. Overall, these data suggest that reduced activity of TPI leads to an oxidized redox state in these mutants and that the alleviation of this stress using reducing compounds can improve the mutant phenotypes.